“ТөРИйн аЛБан ХааГЧ”-Ийн ИМИЖ БҮРдҮҮЛЭЛТИйн ҮйЛ Явцад ХЭвЛЭЛ МЭдЭЭЛЛИйн ХЭРЭГСЛИйн нөЛөө - У.БАТЦЭРЭН (Politology, 2023)
In the latest of the 90s politicians and public servants who formed their own image through the press and media such including with TV, radio and journals or magazines, in the nowadays, they have been using internet based communication environment in forming their imageology and status bechaviour. However, the stateof the- nature of cyberia is performed by the most prefereable trends in the forming imageology of public servants, which is the major tools of the press and media for their performance. The imageology of public servants should be defined by the two types of determinations such as tolerances and outreach to the public and and social demands in the general tendency and its quality of posters, broadcasting and publication and further perfomance of imageology of public servants. Contemporary image of public servants is the major attention to the press and media which is performing the main part of the social appearances. Товч агуулга: 1990-ээд оны сүүлээр телевиз, радио, сэтгүүл зэрэг хэвлэл мэдээлийн хэрэгслийг ашиглан улс төрчид болон төрийн албан хаагчид өөрийн имижээ бүрдүүлж байсан бол өнөө үед интернэт орчинг илүүтэй ашиглаж байна. Учир нь цахим орчинг хэвлэл мэдээллийн нэгэн хэрэгсэл хэмээн үзэх хандлага бий болсон цагт төрийн албан хаагчийн имижийг бүрдүүлэхэд хэвлэл мэдээллийн хэрэгслийн үүрэг маш чухал юм. Хэвлэл мэдээллийн хэрэгслээр цацагдаж буй нийтлэл, нэвтрүүлэг, зурагт хуудас зэргийн чанар, ерөнхий чиг хандлага нь олон нийтэд хэрхэн хүрч байгаа болон нийгмийн шаардлагад хэрхэн нийцэж байгаагаар төрийн албан хаагчийн имиж нь тодорхойлогдох боломжтой юм. Өнөө үеийн төрийн албан хаагчийн имиж нь хэвлэл мэдээллийн хэрэгслийн анхаарлын төвд байдаг нийгмийн үзэгдэл юм.